MAXIMIZING PROFIT POTENTIAL IN SUPPLY CHAIN FROM SUPPLIER-RETAILER INVENTORY REPLENISHMENT IN RURAL AREAS - Encho, Leo Tanyam; Okolo, Abraham; Asogwa, Oluchukwu C.; Christopher, C. C. (FUDMA Journal of Sciences, 2024)
Successful collaborative relationship enhances profitability in the delivery of products or services to customers in a supply. This study focuses on the impact of successful relationships in supply chain management on customer exploration and profitability. By implementing a strong strategy, more customers can be brought into the supply chain, leading to increased productivity and ultimately, higher profitability. The main objective is to determine the optimal quantity levels in supplier relationships that minimize long-term costs in the supply chain. A mathematical model incorporating shipment consolidation was utilized to derive the profit function. Numerical examples were then employed to illustrate the developed models. The results demonstrate variations in total quantity and relevant costs based on factors such as retailer input, supplier replenishment quantities, optimal order quantities, and total relevant costs within the supply chain, ultimately contributing to enhanced profitability. Our result shows that. there is an increase in the supply chain profitability when the retailer orders greater number of items from the supplier.